Is the Text of Ibn Lūqā “A New Evidence” on Pulmonary Circulation Discovery? - Acıduman, Ahmet; Yıldız, Abdullah; Tuzcu, Kemal; Kırlangıç, Hicabi (European Journal of Therapeutics, 2023)
Objective: The discovery of the pulmonary circulation is one of the most important issues in the history of medicine. Recently, an article appeared comprising an assertion that this discovery may have been made before Ibn al-Nafīs by Qusṭā b. Lūqā. The purpose of our study is to examine the text of Qusṭā b. Lūqā to ascertain whether it offers “new evidence” on the discovery of pulmonary circulation. Methods: A comprehensive analysis of the text Qusṭā b. Lūqā and its different copies referenced for the discovery made by Qusṭā b. Lūqā has been made regarding the history of medicine. Results: While Qusṭā b. Lūqā’s text contains detailed descriptions of cardiovascular anatomy, the terminologies and concepts employed were consistent with the prevailing medical knowledge of his time. From the perspective of the history of medicine, it can be said that Qusṭā b. Lūqā’s text does not sufficiently differentiate from those of his predecessors’ regarding the issue of pulmonary circulation. In addition, Qusṭā b. Lūqā mentions the sources he used in his text and does not explicitly claim that he made a discovery different from them. Conclusion: With the available findings, it is difficult for now to say that Qusṭā b. Lūqā discovered the pulmonary circulation in the referenced text.